Avaliação da atividade da alternagina C na inflamação crônica em camundongos - Rabelo, Luis Fernando Gonçalves (2015)
Inflammation and angiogenesis act concomitantly in several chronic diseases. Most of steps of these processes are mediated by integration between extracellular matrix and integrin receptors. Alternagin-C (ALT-C), is a disintegrin-like derived from the venom of Bothrops alternatus. Studies with ALT-C have showed effects in cell adhesion mediated by collagen type I and ability of modulate growth factors associated integrin α2β1. Our aim was to investigate the effects of ALT-C on key components of inflammatory angiogenesis in the murine sponge model. Polyester-polyurethane sponges, used as framework for fibrovascular tissue growth, were implanted in Balb/c mice. Treatment with ALT-C inhibited the main components keys fibrovascular tissue (inflammation and angiogenesis) induced by synthetic subcutaneous implants and also changing the fibrogenic component. Anti-inflammatory effects were observed by inhibition of mast cell and NAG (macrophage activity), and also by the inhibition of cytokines TNF-α and MCP-1 and chemokine CXCL-1. The reduction in hemoglobin content, number of vessels and the concentrations of VEGF and FGF cytokines, have shown that ALT-C is also anti-angiogenic. All these factors show that Alt-C is a strong candidate for the development of anti-inflammatory and anti-angiogenic therapies